Determinants of English Language Proficiency: A Multifaceted Analysis - Panomporn Vajirakachorn; Akaraphun Ratasuk; Krittiya Anuwong (Emerging Science Journal, 2023)
This study investigates the determinants of English language proficiency among students at Panyapiwat Institute of Management (PIM) in accordance with the Common European Framework of Reference for Languages (CEFR) standards. The determinant factors under examination encompass students' attitudes, prior English language knowledge, information-seeking behavior, satisfaction with English language learning, teachers' expertise, teacher readiness, teaching methodologies, familial support, environmental factors, and international exposure. Data were gathered through a survey administered to 469 PIM students, and the analysis employed Partial Least Squares Structural Equation Modelling. The findings revealed that five significant factors influence PIM students' English proficiency, namely their prior English language knowledge, inclination toward seeking knowledge, teachers' expertise, classroom environment, and practical language usage experiences. Additionally, the research demonstrated a noteworthy impact of students' Grade Point Average (GPA) and the time dedicated to learning English on their CEFR scores. This study contributes to the field by shedding light on the multifaceted factors influencing English language proficiency among PIM students, offering insights that can inform language education strategies and policies. It emphasizes the importance of prior knowledge, information-seeking behavior, teacher quality, classroom environment, and practical language application in enhancing English language skills. Doi: 10.28991/ESJ-2023-SIED2-020 Full Text: PDF